PENURUNAN KADAR MINYAK DAN LEMAK PADA LIMBAH CAIR KANTIN MENGGUNAKAN METODE ADSORPSI ZEOLIT (Jurnal Kesehatan Siliwangi, 2021)
Canteen activities at PT. XYZ includes washing of cooking utensils and washing of employees tableware and doesn’t have processing of canteen liquid waste. The results of laboratory tests carried out on the liquid waste of the canteen contains oil and fat content of 10 mg/L, so processing is needed before being flowed into river using grease trap with zeolite modified. The purpose of this study is to reduce the levels of oil and fat in the liquid waste of the canteen using a zeolite modified grease trap using a zeolite thickness of 30, 40, and 50 cm. This research is an experimental study with a research design is pre-test post-test without control and the sampling technique used is composite sampling. Sample in this study was some of the canteen liquid waste at PT. XYZ given treatment The statistical test used is one way anova test. Based on the results, it’s known that the percentage of reduction in oil and fat levels in thickness of zeolite 30 cm is 77.8%, thickness of zeolite 40 cm is 83.5%, and thickness of zeolite 50 cm is 92.9%. Zeolite thickness of 50 cm is the most effective thickness in reducing oil and fat content. Based on statistical tests it’s known that there is a difference variation of zeolite thickness to decrease in oil and fat content due to P-value of 0.0005 so that ≤ α (0.05). Industry can apply canteen liquid waste treatment using grease trap modified and carry out regular maintenance of equipment.